2014
DOI: 10.4103/2141-9248.126610
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute respiratory tract infections in under-five children in Enugu Southeast Nigeria

Abstract: Background:Acute respiratory tract infections (ARIs) constitute the major causes of mortality and morbidity among under-five children of the developing world. The prevalence of ARIs is determined individually or collectively by a number of factors which may be prevalent in our environment.Aim:The present study is aimed to determine the risk factors that affect the prevalence of ARIs in under-five children in Enugu.Subjects and Methods:A cross-sectional study of 436 under-five children diagnosed with ARI was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
122
10
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(181 citation statements)
references
References 16 publications
42
122
10
7
Order By: Relevance
“…Most cases of ARIs seen in our study were upper respiratory tract infections which is consistent with the reports by other authors [9]. The cases of pneumonia seen in our review was comparable to the findings by Acharya et al [9] and Zaman et al [10] in South India [18] in Enugu. This difference may the due to the differences in the methodology.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Most cases of ARIs seen in our study were upper respiratory tract infections which is consistent with the reports by other authors [9]. The cases of pneumonia seen in our review was comparable to the findings by Acharya et al [9] and Zaman et al [10] in South India [18] in Enugu. This difference may the due to the differences in the methodology.…”
Section: Discussionsupporting
confidence: 83%
“…Our study was a retrospective review of all ARI cases seen at the ARI clinic of the UPTH (University of Port Harcourt Teaching Hospital) and therefore some cases of pneumonia seen at the emergency ward were not included while the study by Ujunwa and Ezeonu [18] was a prospective study carried out in 3 hospitals in Enugu metropolis and only children less than 5 years were recruited in their study. In our study, most of the children presenting with ARI were under five years of age with most of them being infants which is similar to the findings by other authors [16,18,21]. This may be attributed to the fact that younger children are less immune competent compared to the older children and are therefore more likely to get infected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also consistent with a similar study carried out in Kenya by which reported that the prevalence of ARI was higher in children living in urban areas as compared to these living in rural areas. The significance of these three variables in relation to ARI was also reported and supported by [10] who carried out an analysis of risk factors for Acute Respiratory Tract Infection (ARTI) in children less than 5 years in Enugu south east of Nigeria.…”
Section: Exploring Ari By Various Risk Factors (Bivariate Analysis)mentioning
confidence: 98%